2001
DOI: 10.1042/bj3540067
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose and light regulation of a cold-inducible UDP-glucose pyrophosphorylase gene via a hexokinase-independent and abscisic acid-insensitive pathway in Arabidopsis

Abstract: UDP-glucose pyrophosphorylase (UGPase) is a key enzyme producing UDP-glucose, which is involved in an array of metabolic pathways concerned with, among other functions, the synthesis of sucrose and cellulose. An Arabidopsis thaliana UGPase-encoding gene, Ugp, was profoundly up-regulated by feeding sucrose to the excised leaves and by an exposure of plants to low temperature (5°C). The UGPase activity and its protein content also increased under conditions of sucrose feeding and exposure to cold. The sucrose ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
1
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 38 publications
3
56
1
4
Order By: Relevance
“…Tight coupling exists between P i and sugar metabolism and several studies have shown an interaction between sugar metabolism and P i -regulated gene expression (Sadka et al, 1994;Nielsen et al, 1998;Ciereszko et al, 2001aCiereszko et al, , 2001bLejay et al, 2003;FrancoZorrilla et al, 2004;Liu et al, 2005;Mü ller et al, 2005). Such interactions could rely on a secondary effect; for example, sugar added may operate as a scavenger, influencing the level of P i and thereby the expression of any P-regulated gene.…”
Section: General Features Of the P Starvation And Sugar Treatment Expmentioning
confidence: 99%
See 2 more Smart Citations
“…Tight coupling exists between P i and sugar metabolism and several studies have shown an interaction between sugar metabolism and P i -regulated gene expression (Sadka et al, 1994;Nielsen et al, 1998;Ciereszko et al, 2001aCiereszko et al, , 2001bLejay et al, 2003;FrancoZorrilla et al, 2004;Liu et al, 2005;Mü ller et al, 2005). Such interactions could rely on a secondary effect; for example, sugar added may operate as a scavenger, influencing the level of P i and thereby the expression of any P-regulated gene.…”
Section: General Features Of the P Starvation And Sugar Treatment Expmentioning
confidence: 99%
“…Feeding P i to excised leaves also decreased the AGPS2 transcript level by antagonizing the induction by Suc (Nielsen et al, 1998). In Arabidopsis, the impact of P on C metabolism has been exemplified by P starvationinduced expression of genes for b-glucosidase (Malboobi and Lefebvre, 1997), UDP-Glc pyrophosphorylase (UGPase), and the small subunit of ADP-Glc pyrophosphorylase (Ciereszko et al, 2001a(Ciereszko et al, , 2001b, and sugar induction of a P i transporter has been demonstrated in Arabidopsis roots (Lejay et al, 2003). Recently, we have shown for Arabidopsis that the sugar-inducible genes encoding b-amylase (BMY1) and chalcone synthase (CHS) are also induced by P deficiency and are more strongly regulated by sugars when leaf segments originate from P-starved plants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of gene At3g03250 is known to be regulated by light as well as phosphate and sucrose concentration [13][14][15] . In addition, in vitro oligomerization of UDPGP has been shown to influence the activity of this enzyme; the most active form being the monomer 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In the banana, UGPase genes are up-regulated by ethylene (50), whereas UGPase genes are up-regulated by phosphate deficiency, light exposure, and sucrose supplementation in the potato (51,52). In this study, we evaluated the correlation between the sucrose content and ScUGPase-1 gene expression in the sugarcane cultivars RB855156 (with a higher sucrose content) and RB935744 (with a lower sucrose content), but the ScUGPase-1 profiles were very similar in these cultivars.…”
Section: Discussionmentioning
confidence: 99%